Half Mode Substrate Integrated Waveguide (HMSIW) Bandpass Filter - Wang, Yuanqing; Hong, Wei; Dong, Yuandan; Liu, Bing; Tang, Hong Jun; Chen, Jixin; Yin, Xiaoxin; Wu, Ke (IEEE microwave and wireless components letters, 2007)
This letter presents the design and experiment of the half mode substrate integrated waveguide (HMSIW) bandpass filters. Three-pole and five-pole HMSIW filters are simulated by using CST software and fabricated with a single layer standard printed circuit board process. Different external-coupling approaches are adopted in the design of the two filters. The measured results are in good agreement with the simulated results. Low insertion loss and good selectivity are achieved